Grape juice concentrate (G8000®) intake mitigates testicular morphological and ultrastructural damage following cadmium intoxication. Issue 5 (30th October 2015) - Lamas, Celina A.; Gollücke, Andrea P.B.; Dolder, Heidi
Summary: Cadmium is a well‐known testicular toxicant, and parts of the world population are exposed chronically by inhalation or by food and water intake. Grape products have been highlighted as important sources of bioactive compounds, having anti‐inflammatory, anti‐oxidant and metal chelating properties. Since maintenance of tissue morphology is essential for testicular sperm development and hence male fertility, we analysed the protective effect of grape juice concentrate (GJC) (G8000 ® ) consumption on testicular morphology in rats exposed to cadmium. Thus, four groups of male Wistar rats ( n  = 6 per group), 50 days old, ingested either water or G8000 ® (2 g/kg/day) until they had completed one spermatogenic cycle in adult life (136 days old). Cadmium (1.2 mg / kg) was injected intraperitoneally when the animals were 80 days old into one of the water and one of the G8000 groups; intraperitoneal saline was used as a control in the other two groups. Animals anaesthetised and exsanguinated at 136 days and then perfused with Karnovsky's fixative and then the testes were collected for morphological analysis. We describe evident disruption of testicular morphology by cadmium, with alteration in tissue component proportions, reduced Leydig cells volume and initial signs of an inflammatory process. Ultrastructural analysis showed greater damage, suggesting spermatogenesis disruption. G8000 ® ingestion allowed tissue architecture to be re‐established, as was corroborated by our stereological and morphometric findings. Animals from the group where G8000 ® had been administered together with cadmium revealed a significant reduction in macrophages and blood vessel volume, suggesting diminished inflammation, when compared to animals that received only cadmium. Moreover, smaller number of ultrastructural alterations was noted, revealing fewer areas of degeneration and disorganized interstitium. In conclusion, our results demonstrate that GJC consumption prevented the spermatogenic disruption promoted by cadmium, and thus could be a promising form of therapy against male infertility.